The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/jid.2008.460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Stressors on Psoriasis: A Prospective Study

Abstract: Hypotrichosiswith juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 20 publications
8
66
0
4
Order By: Relevance
“…In particular the unpredictable course of a skin condition and the lack of control can make coping more difficult. In line with research on other chronic physical conditions there is some indication that a more passive, avoiding coping style and catastrophizing cognitions can negatively affect the course of a condition and the success of a treatment [7,8,25,28]. Furthermore, studies in people with atopic eczema and psoriasis have revealed connections between perceived helplessness in coping with the condition and decreased physical and psychological well-being [2].…”
Section: R D I S T R I B U T I O Nmentioning
confidence: 69%
See 1 more Smart Citation
“…In particular the unpredictable course of a skin condition and the lack of control can make coping more difficult. In line with research on other chronic physical conditions there is some indication that a more passive, avoiding coping style and catastrophizing cognitions can negatively affect the course of a condition and the success of a treatment [7,8,25,28]. Furthermore, studies in people with atopic eczema and psoriasis have revealed connections between perceived helplessness in coping with the condition and decreased physical and psychological well-being [2].…”
Section: R D I S T R I B U T I O Nmentioning
confidence: 69%
“…Accordingly, in patients with atopic eczema, subjective stress proved to predict disease severity on the following day [26]. Additionally, in patients with psoriasis, high levels of daily stressors were associated with an increase in disease severity and itch four weeks later [24,25]. Stressors can influence wound healing [27], although this relationship has not been studied in patients with skin conditions.…”
Section: Psychosocial Factors In Dermatological Conditionsmentioning
confidence: 99%
“…A bevezetőben említett, a betegségüket saját bevallásuk szerint stresszérzékenynek, illetve a nem stresszérzékenynek tartó pikkelysömörös betegek közöt-ti klinikai különbségek ismeretében érdekes megvizsgál-ni, hogy a két csoport közötti különbség a hormonok szintjén is megjelenik-e. Richards és mtsai azt találták, hogy a betegségüket stresszérzékenynek vallók stresszor előtti bazális kortizolszintjei alacsonyabbak voltak, és a stresszre is csökkent kortizoltermeléssel reagáltak [56]. Verhoeven és mtsai pedig azt a megfi gyelést tették vizsgá-latukban, amely az egyetlen, eddig a témában elkészült prospektív tanulmány, hogy az egy hónappal korábban magasabb stressz-szintről beszámoló betegek tünetei sú-lyosabbak, kortizolszintjük pedig alacsonyabb volt a következő vizit alkalmával [10]. Ez felveti, hogy a pikkelysömörös betegekben megfi gyelt pszichológiai kü-lönbségek hormonális eltérésekben is manifesztálódnak: alacsonyabb kortizolválasszal reagálnak egy-egy streszszorra, ami hajlamosíthatja őket a tüneteik stressz hatá-sára bekövetkező fellángolására.…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…Fontos azonban megjegyezni, hogy más szerzők nem találtak kapcsolatot az életesemények és a tünetek súlyos-sága között, és eddig sem az ok-okozati kapcsolatot, sem a folyamat hátterében álló pontos patomechanizmust nem sikerült egyértelműen bizonyítani [10,11]. Ezt részben magyarázhatja, hogy sok vizsgálat redukcionista: vagy csak a biológiai, vagy csak a pszichológiai jelensége-ket veszi fi gyelembe, pedig a stressz indukálta fi ziológiai válaszok szubjektumfüggőek.…”
unclassified
“…A prospective study showed that severity of psoriasis was associated with severity of stress. 49 Stress not only leads to clinical exacerbation but also has negative effects on efficacy of therapy. Fortune et al reported that stress can decrease the efficacy of psoralen ultraviolet A (PUVA).…”
Section: Stressmentioning
confidence: 99%